Analysis of Differences in the Investment Intention Characteristics Based on Gender - Gladys Greselda Gosal; Jesslyn Beatricia Ivana Tania (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
Along with the rampant investment trends among millennials, questions arise regarding whether there are differences in the characteristics of investment intention between males and females. This study uses independent samples t-test to try to answer those questions, using risk aversion and locus of control as predictors of investment intention. Questionnaires were distributed to Universitas Ciputra’s students in management study program who have participated in investment webinars and therefore have knowledge about investment. 91 samples were collected using purposive sampling. The findings indicate that females are more risk averse and tend to have external LOC, therefore they are less likely to invest compared to males. Furthermore, risk aversion will be more dominant in males who have external LOC, while risk aversion will be very dominant for females who have internal LOC. These findings conclude that there is significant difference in the characteristics of investment intention between males and females.